Fructokinase from rat liver. I. Purification and properties - Sánchez, J.J. (1971)
Fructokinase (ATP:d-fructose-1-phosphate transferase, EC 2.7.1.3) from rat liver has been purified 400-fold. The purification procedure involves an acid treatment, a heat step at 65°, (NH4)2SO4 fractionation, chromatography on Sephadex G-100 and finally (NH4)2SO4 extraction. The enzyme appears nearly homogenous by density gradient centrifugation but gives a single peak in sedimentation velocity analysis. Purified liver fructokinase has a Km of 0.46-0.80 mM for fructose and 1.56-1.33 mM for MgATP at a K+ concentration of 0.4 and 0.1 M, respectively. The enzyme also phosphorylates l-sorbose and d-tagatose. No difference could be found in the phosphorylation of the pyranose and furanose forms of fructose. The enzyme is inhibited by p-chloromercuribenzoate and is stable up to 50-55°. © 1971.